Analytical method development of pitavastatin-loaded SNEDDS formulation: Multivariate analysis regarding ultraviolet spectrophotometry analysis - Rohman., Abdul (Journal of Food and Pharmaceutical Sciences, 2019)
Herein, this work aimed to develop and assess feasibility of multivariate model of partial least square analysis for specific quantification of pitavastatin (PVT)-loaded self-nano emulsion (SNE) formulation using UV-Vis spectrophotometry.    PVT loaded into self-nano emulsion formulation comprising of Capryol-90, Tween 80, and Transcutol P under different loading levels i.e. 10-90 mg/mL. All samples scanned using UV-Vis spectrophotometer from 300-200 nm. PVT and SNE were prepared separately for estimation of interference. Multivariate model was constructed using partial least square (PLS) regression analysis as well as principal component analysis for qualitative pattern recognition. Cross-validation using a leave one out technique and goodness of fit parameters were applied for model evaluation.    The results revealed that maximum sensitivity of PVT was obtained at 244 nm. SNE formulation had different interference value and decreased exponentially as increasing the PVT loading in the SNEDDS formulation. The highest drug loading had an interference value of 7.11%. Therefore, the SNEDDS formulation interfered the PVT quantification and mainly depended on the drug loading. Finally, multivariate analysis, PLS could be applied to eliminate the placebo/formulation interference for PVT quantification independently towards drug loading level.